Wpływ pandemii COVID-19 na płynność akcji notowanych na Giełdzie Papierów Wartościowych w Warszawie - Marcin Tuszkiewicz (Finanse i Prawo Finansowe, 2022)
The aim of the article is to verify the impact of the COVID-19 pandemic on stock liquidity on the Warsaw Stock Exchange (WSE). In addition the article tries to assess whether the WIG20 index includes companies with the most liquid quotations.